2023
DOI: 10.1002/1873-3468.14722
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic transport at the crossroads of proteostasis, neurodegeneration and neuroprotection

Paulo A. Ferreira

Abstract: Nucleocytoplasmic transport comprises the multistep assembly, transport and disassembly of protein and RNA cargoes entering and exiting nuclear pores. Accruing evidence supports that impairments to nucleocytoplasmic transport are a hallmark of neurodegenerative diseases. These impairments cause dysregulations in nucleocytoplasmic partitioning and proteostasis of nuclear transport receptors and client substrates that promote intracellular deposits – another hallmark of neurodegeneration. Disturbances in liquid–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 226 publications
0
12
0
Order By: Relevance
“…1,9,10 Notably, dysregulations of the moonlighting activity of CY of Ranbp2 cause proteostatic imbalances of a restricted set of client substrates, which are implicated in neuroprotection, and some of these substrates are also affected in mice with haploinsufficiency of Ranbp2. 1,10,114 Third, Ranbp2 plays a selective role in chorioretinal proteostasis by mechanisms that are not well understood. For example, the CLD of Ranbp2 specifically associates to a subset of ATPase and non-ATPase subunits of the 19S cap of the proteasome selectively in retinal extracts but not in other tissue extracts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,9,10 Notably, dysregulations of the moonlighting activity of CY of Ranbp2 cause proteostatic imbalances of a restricted set of client substrates, which are implicated in neuroprotection, and some of these substrates are also affected in mice with haploinsufficiency of Ranbp2. 1,10,114 Third, Ranbp2 plays a selective role in chorioretinal proteostasis by mechanisms that are not well understood. For example, the CLD of Ranbp2 specifically associates to a subset of ATPase and non-ATPase subunits of the 19S cap of the proteasome selectively in retinal extracts but not in other tissue extracts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We focused on proteostatic impairments affecting the RPE and the retina for several reasons. First, these tissues are chronically exposed to and vulnerable to environmental insults (e.g., photo-oxidative stress) and thus predisposed to proteotoxicity and AMD. , AMD is a multifactorial disease characterized by the induction of heat shock proteins, the formation of large laminar heterogeneous aggregates (drusen) with aging, and by the irreversible loss of photoreceptor neurons and RPE cells. , Second, we have previously shown that haploinsufficiency of Ranbp2 preordains these tissues to neuroprotection against proteostatic stressors, such as photo-oxidative stress. ,, Notably, dysregulations of the moonlighting activity of CY of Ranbp2 cause proteostatic imbalances of a restricted set of client substrates, which are implicated in neuroprotection, and some of these substrates are also affected in mice with haploinsufficiency of Ranbp2 . ,, Third, Ranbp2 plays a selective role in chorioretinal proteostasis by mechanisms that are not well understood. For example, the CLD of Ranbp2 specifically associates to a subset of ATPase and non-ATPase subunits of the 19S cap of the proteasome selectively in retinal extracts but not in other tissue extracts. Loss of small ubiquitin-like modifier-1 (SUMO-1)-binding activity of CLD caused by mutations in the consensus SUMO-1-interacting motif (SIM), which overlaps with the internal repeat 1 (IR1) of Ranbp2 (Figure a), protects photoreceptor neurons from death against phototoxicity, but unlike Ranbp2 haploinsufficient mice, photoreceptors are not protected from photodamage. , Further, loss of CY PPIase activity of Ranbp2 diminishes the levels of polyubiquitylated substrates in the retina and RPE, whereas neither the selective loss of Ranbp2 in motoneurons nor the constitutive loss of its CY PPIase activity affect, respectively, the overall levels of polyubiquitylated substrates in sciatic nerves and liver. , Hence, the Ranbp2 scaffold appears to regulate proteostasis and neuroprotection to stressors by coupling modular activities of CY and CLD (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations